Chronicles of the Egyptian revolution : and its aftermath : 2011-2016 - Bassiouni, M. Cherif (Cambridge University, 2017)
"This book is about the Egyptian people's 2011 Revolution for freedom, justice, and human dignity, and its aftermath. The Revolution succeeded in toppling the authoritarian Mubarak regime in less than three weeks. It was then co-opted by the Muslim Brotherhood through Egypt's first free and fair elections in 2012, which was in turn crushed in 2013 by a popularly supported military regime whose practices of repression negatively impacted the justice system and human rights. The problems facing the country and its people are daunting, particularly economic, demographic, and social pressures. The contextual analysis of these and other historic and contemporary issues give the reader a comprehensive understanding of what has occurred in the last five years and an insight into where the country is heading. Even though the Revolution has been suppressed and the promise of democracy shunted aside, the majority of the Egyptian people continue to hope for the unachieved dreams of social justice, human dignity, and freedom. Egypt's geopolitical importance makes it indispensable to the stability of the Middle East, and thus important to the world."